TDAH não é “coisa de criança”: Eu, uma professora e pesquisadora com o Transtorno de Déficit de Atenção e Hiperatividade em ambientes não inclusivos - Teixeira, Flávia Cristina Guimarães (2023)
Is ADHD just a kid’s thing? This dissertation aims to narratively understand my experiences as a language teacher with ADHD (Attention Deficit Hyperactivity Disorder) and how this condition impacts a large part of my life, especially my teaching practices, my professional and academic relationships in the context of diversity. In this research, which follows the theoretical-methodological path of narrative inquiry I inquire my experiences according to Clandinin and Connelly (2015), which allow me to understand and experience erasure, invisibilization and inclusion (sometimes in the same environment) both as a teacher and a master's student with ADHD. What prompted me to carry out this research was the experience of the narrative “Ah… the look of that teacher…”, in which I discovered that some characteristics of ADHD allowed me to be included, an experience I had never previously experienced. This narrative awakened in me how (not) inclusive my practices were, because by recognizing and understanding my specificities I was willing to become a teacher more attentive to inclusive practices, that is, looking at diversity with respect to specificities. Having to adapt my behaviors to what have long been established as social standards of behavior (Dewey, 1976) is a great challenge when I have to discover on my own how to feel like I belong in non-inclusive contexts. ADHD is perceived differently in each person and according to Barkley (2022), knowing everything possible about the nature of the disorder, knowing what can change and what cannot, makes life easier in many aspects. As my research is predominantly autobiographical in nature, I highlight characteristics of ADHD that are most significant to me, such as hyperfocus, defined by Silva (2009) as the ability to hyperconcentrate on ideas and contexts, and creativity, which often help me to balance the lack of sense of time and the paralysis of ADHD (ADDA), so common that they are already part of my personal description. Dealing with ADHD is very uncomfortable for me, as I am a mixed type, hyperactive and impulsive with attention instability (Silva 2009), with a predominance of mental hyperactivity in which my mind looks more like a computer screen with dozens of tabs open, background music and a movie playing. I always want to do many things because I feel encouraged to do them, in the same proportion that I withdraw into myself so deeply that surviving is no longer a priority. During my research, by reading and understanding more about the disorder, I was able to identify it and ask for help. The support network was fundamental throughout this journey. Understanding ADHD as part of my identity had an unexpected trajectory during the research. I think I expected little from it, because deep down, I wasn't sure if I would finish it, but I did.